A re‐appraisal of publication rates of scientific papers presented at the Otorhinolaryngology Research Society meetings. (22nd February 2016) - Lau, A.S.; Krishnan, M.; Williams, S.P.; Mamais, C.; Sweed, A.; Bhat, J.; Somashekar, S.; Leong, S.C.
Abstract : Objectives: To review the rate of publication of papers in peer‐reviewed journals after oral presentations at the Otorhinolaryngology Research Society meetings between 1996 and 2013 and to compare trends with the previous review (1979–1995). Design: Literature review. Setting: Merseyside ENT Research Collaborative. Participants: The abstracts of presentations at Otorhinolaryngology Research Society meetings are published in Clinical Otolaryngology. A structured search of PubMed was undertaken to identify published Otorhinolaryngology Research Society presentations. Main outcome measures: Publication rates. Results: A total of 460 abstracts were identified. The interobserver reliability among reviewers was 98%. Of the total, 259 (56.3%) abstracts were published in peer‐reviewed journals. The average time from Otorhinolaryngology Research Society presentation to publication was 27.7 months (median 23), which was not significantly different from the previous review. Publication by subspeciality was as follows: head and neck (45.6%), otology (30.5%), rhinology (22%) and others (1.9%). Most published Otorhinolaryngology Research Society presentations were published in Clinical Otolaryngology (22.4%), followed by the Journal of Laryngology and Otology (8.1%) and the Laryngoscope (7.3%). Clinical research was the most common category of abstracts being presented at Otorhinolaryngology Research Society meetings, followed by laboratory‐based research. Over half (56.5%) of laboratory research presented were head and neck themed, while otology and rhinology predominated clinical research presentations. Over half (52.1%) of Otorhinolaryngology Research Society abstracts originated from units in the North of England. Bristol presented the most abstracts (30.1%), followed by Newcastle (25.1%). Conclusions: The publication rate of Otorhinolaryngology Research Society presentations remains high and many are subsequently published in high‐impact factor otolaryngology journals. More Otorhinolaryngology Research Society presentations are now published in American and European journals.